Analyse des freins à l’adoption des SPOC en classes inversées - Narjes Sassi; Caroline Cloonan (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The flipped classroom became a very common teaching method used in higher education establishments. In the flipped classroom, students are given online contents to consult which are later used in face-to-face sessions. It seems that this method allows a better quality of exchange and a deepening knowledge as well as a greater autonomy and empowerment of learners who can assimilate content before face-to-face sessions. Despite these advantages, setting up flipped classrooms using Small Private Online Course (SPOC) may suffer from some resistance from teachers and students.Indeed, obstacles to the adoption of these new pedagogical methods can hinder its advantages. We analyze these brakes thanks to the feedback of pedagogical managers in a business school who supervised the implementation and the follow-up of flipped classroom using SPOC. Results from qualitative data analysis distinguish and qualify the obstacles from the teachers’ and students’ point of view. For teachers the main obstacles were : a) the pedagogy transformation and the teaching paradigm change, (b) the difficulty for the appropriation of a content that they have not developed, (c) the uncertainty about the quality of available learning metrics to assess learners’ level of understanding on the SPOC, (d) the uncertainty that the SPOC is used by their school to cut teaching hours. For students these obstacles are related to: (a) the organization and the autonomy of their personal work, (b) the delayed interaction with a teacher, and (c) the misunderstanding of the interest of blended classroom model and the use of SPOC compared to a traditional classroom setting.